Pediatric turbinoplasty: what is the impact of allergy on long-term outcomes? - Sousa, Francisco Alves de; Azevedo, Sara Raquel; Costa, Sara; Pinto, Ana Nóbrega; Soares, Teresa; Coutinho, Miguel Bebiano; Meireles, Luís (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2022)
Background: The use of inferior turbinoplasty (IT) in pediatric patients is controversial, especially in the presence of allergic rhinitis. The objective of this study was to assess the long-term results of radiofrequency inferior turbinoplasty in allergic versus non-allergic children. Methods: Children operated between 2017 and 2019 and whose intervention included radiofrequency IT were included. Multiple scores were collected in 2021 through a telephone call to parents. A comparison was made between allergic children (AC) and non-allergic children (NAC). Results: 41 children were included. Parents of AC reported a higher degree of dissatisfaction with surgery (AC: 0.8±1 verses NAC: 0.2±0.5, p=0.026). AC revealed a greater dependence on medication in order to control nasal obstruction (41% in AC vs 6% in NAC, p=0.010). The total Nasal Obstruction Symptom Evaluation (NOSE) score was higher in AC (mean AC 26±25 verses mean NAC 5±12, p=0.003). The sinus and nasal quality of life 5 SN-5 score was higher in AC (mean AC 2.5±1 vs NAC mean 1.4±0.8, p<0.001).AC had a lower score on the SN-5 quality of life scale (mean AC 6.6±2.4 vs NAC mean 8.3±1.8, p=0.014). Conclusions: Radiofrequency IT alone does not seem effective in the long-term resolution of nasal obstruction in AC.